2015
DOI: 10.1002/ajpa.22826
|View full text |Cite
|
Sign up to set email alerts
|

Dietary practices in ancient populations from northern Chile during the transition to agriculture (Tarapacá region, 1000 BC–AD 900)

Abstract: A gradual transition to crop consumption, especially maize, is suggested. This complemented the earlier hunter-gatherer tradition of marine resources and wild fruit consumption. Contrarily to the predictions made by some archaeologists, the results obtained for northern Chile contrast with the classical perspective of a "Neolithic Revolution" in which transition to agriculture occurred more abruptly and linearly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0
7

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 22 publications
3
19
0
7
Order By: Relevance
“…However, the inland sites of the Formative, Middle Horizon, and Late‐Intermediate period are characterized by very variable in utero increment values. Their wide‐ranging δ 15 N and δ 13 C values probably derive from the dietary heterogeneity seen in the adults during these time periods (King et al, ; Pestle et al, ; Santana‐Sagredo, Lee‐Thorp, et al, ; Santana‐Sagredo, Uribe, et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the inland sites of the Formative, Middle Horizon, and Late‐Intermediate period are characterized by very variable in utero increment values. Their wide‐ranging δ 15 N and δ 13 C values probably derive from the dietary heterogeneity seen in the adults during these time periods (King et al, ; Pestle et al, ; Santana‐Sagredo, Lee‐Thorp, et al, ; Santana‐Sagredo, Uribe, et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…We sampled individuals from all archaeological periods, due in part to knowledge that preservation of collagen in early periods is variable (King et al, ). Previous isotopic work has also indicated that agricultural staples, such as maize, played a variable part in the adult diet through time (King et al, ; Pestle, Torres‐Rouff, Hubbe, & Smith, ; Santana‐Sagredo, Hubbe, & Uribe, ; Santana‐Sagredo, Lee‐Thorp, Schulting, & Uribe, ; Santana‐Sagredo, Uribe, Herrera, Retamal, & Flores, ), and it is likely that this variation also extends to childhood diet. By sampling widely, and including later archaeological phases, we increase the likelihood of identifying complementary feeding using maize, and the possibility of seeing changes to stress levels through time.…”
Section: Methodsmentioning
confidence: 97%
“…For Formative infants living in inland ravines, however, it is unlikely the predominance of marine resources in their first foods but C3 plants. Analyses of milling material of Guatacondo village identified mainly Prosopis starches but not maize (Tartaglia, ), whereas in Tarapacá, the maize acquired greater importance only towards the Late Formative (Santana‐Sagredo et al, ; Vidal, Hinojosa, Pérez, Peralta, & Uribe, ).…”
Section: Discussionmentioning
confidence: 99%
“…Excellent preservation of human remains recovered from Tr‐40 has allowed for identification and analysis of noteworthy palaeopathological findings (Allison, Gerszten, Munizaga, Santoro, & Mendoza, ; Allison, Gerszten, Shadomy, Munizaga, & Gonzalez, ; Fontana, Allison, Gerszten, & Arriaza, ; Munizaga, Allison, & Aspillaga, ; Munizaga, Allison, & Paredes, ; Rothhammer, Allison, Núñez, Standen, & Arriaza, ). More recently, stable isotopes of diet (Santana‐Sagredo, Uribe, Herrera, Retamal, & Flores, ), entheseal changes (González & González‐Ramírez, ) and trauma analysis (Herrera et al, ) have been performed. In contrast to abundant works on adults, nonadults from Tr‐40 remain understudied.…”
Section: Introductionmentioning
confidence: 99%
“…We are not assuming, however, that agriculturalists necessarily had the highest fertility rates. This is because the idea of a Neolithic Revolution, which associates population pressures with the origins of agriculture, may not be a valid assumption in many contexts in Atacama and Mesoamerica , the transition to agriculture occurred gradually and was far from a ‘revolution’, with no demographic increase resulting from such transition at least in populations from Atacama . Similarly, in eastern North America, no population pressure or resource imbalance was discovered to be related to the origins of agriculture .…”
Section: Discussionmentioning
confidence: 99%